Effectiveness of a diabetes education and intervention program on blood glucose control for patients with type 2 diabetes in a Turkish community - Acik, Yasemin; Bulut, Hulya Yildizhan; Gulbayrak, Canan; Ardicoglu, Ozge; Ilhan, Nevin (SEAMEO TROPMED Network, 2004)
This study was undertaken to determine the effects of patient education and other interventions (regular exercise and diet), combined with existing oral antidiabetic therapy, on blood glucose control in patients with type 2 diabetes mellitus (DM). Two out of 16 primary health care centers present in Elazig, an eastern Turkish city, were randomly selected for this study; the patients had type 2 DM, lived in the service area of these health centers. Of a total of 100 participants, 33 were instructed to follow the standard diet for type 2 DM patients, 28 performed exercise in addition to the standard diet, and 39 did not participate in either exercise or follow the diabetic diet; they served as the control group. The percentage of glycosylated hemoglobin (HbA1C) was measured before and after the 8-week program and comparisons between the groups were made. At the beginning of the program, the HbA1C percentage in the diet-plus-exercise group (9.9±2.6%) was higher than in the diet (7.8±2.2%) and control groups (7.5±2.1%). After the intervention program, the HbA1C value of the control group had not changed significantly, while the most dramatic change in this value was obtained in the diet + exercise group, which was significantly reduced to 7.9±1.5%. The results of this 8-week intervention program indicate that a diabetes education and intervention program involving the combination of exercise and diet enhanced the effectiveness oral therapy on blood glucose control in patients with type 2 DM.
Keywords: oral antidiabetic agent; adult; article; blood glucose monitoring; clinical article; clinical trial; controlled clinical trial; controlled study; diabetes mellitus; diet therapy; exercise; female; glucose blood level; health center; health program; human; male; patient education; treatment outcome